Dual-Wavelength Polarization Multifunction Metalens Based on Spatial Multiplexing - Xiangshuo Shang; Haiyang Huang; Yi Zhou; Jiaheng Gong; Yang Liu; Wei Li (Photonics)
Technological advancements have enabled the active control of electromagnetic waves. Metalenses, known for their precision in wavefront shaping and functional versatility, represent a breakthrough in optical modulation. This study addresses the challenge of achieving dual-wavelength multifunctionality in metalens design. We developed and experimentally validated metalenses with polarization dual-function multiplexing at discrete mid-wave infrared wavelengths, demonstrating high phase fidelity and functional versatility. In addition, the proposed design method was extended to long-wave infrared wavelengths, showcasing its adaptability to different application scenarios. The application of spatial multiplexing significantly enhanced the performance of the metalenses, providing a promising solution for efficient and compact optoelectronic devices.